Prosopis juliflora – a potential game changer in the charcoal sector in Kenya - Sola, P.; Njenga, M.; Koech, G.; Wanjira, E.O.; Kirimi, M.; Siko, I.; Bourne, M.; Muriuki, J. (2020)
Prosopis juliflora, locally known as ‘mathenge’, is a shrub or small tree that is native to Mexico, South America and the Caribbean, and is an invasive species in Kenya. In Kenya, Prosopis juliflora was introduced from 1973 through to the 1980s to arid and semi-arid areas to mitigate desertification and fuel wood shortages (Pimentel et al., 2000; Masakha & Wagulo, 2015). The species was preferred because of its resilience, drought tolerance and fast growth (Meyerhoff, 1991). However, it is aggressively invading about 500-1300 ha per year, causing land use and land cover change, and losses of grasslands, woodlands, croplands, grazing lands and settlements, especially in Turkana, Baringo, Garissa, Tana River and Taita Taveta Counties (Mbaabu et al., 2019; Eckert et al., 2020). By 2016, Prosopis juliflora had invaded 2 percent of Kenyan drylands, covering 18 792 hectares in Baringo County alone. In this County, Prosopis juliflora coverage is estimated to have increased by almost 4 percent or 640 ha per year since 2002 (Mbaabu et al., 2019). In Marigat Sub-County, Ng’ambo is the most highly invaded, whilst Ilchamus and Loboi are relatively less affected. Thus, management and utilization of the current 18 792 ha of Prosopis juliflora in Baringo County for charcoal production using improved kilns and effective transportation and marketing presents potential for improving livelihoods and the environment (Mbaabu et al., 2019). Various technologies with high charcoal conversion efficiencies of about 30 percent have been adapted and/or developed by Kenya Forest Research Institute (KEFRI) and other institutions.